COMPARING PROBLEM SOLVING BETWEEN HIGH AND LOW ACHIEVERS TEST TAKERS TO OVERCOME TEST ANXIETY IN TOEFL - Sa'adah Ramadhiyah; Didi Sukyadi (English Language Teaching Department (Prodi Pendidikan Bahasa Inggris), 2018)
Test anxieties cannot be denied by the test takers in TOEFL test. Sometimes, anxieties bring to negative and positive effects to the test takers. Each test taker has the way to solve their problems to overcome their anxieties. However, every problem solving may bring the test takers to successful and unsuccessful. This present study wanted to compare the problem solving between high achievers and low achievers test takers in TOEFL test performance to overcome their anxiety. The quantitative survey research design was used in this study to investigate the difference between both test takers. The researcher used the online questionnaire to collect data from the participants. Moreover, 30 participants were selected purposively by the researcher. The results show that the high achiever test takers are better in solving their problem toward test anxiety. The difference occurs in planning, cognitive, self-efficacy and self-checking problem solving.